(untitled) (Voice: A Biannual & Bilingual Journal, 2024)
This article examines the role of literature in the creation, articulation, and rejection of national identities in Nepal, as inspired by Bhupi’s poem that highlights the relationship between literature and nation-building. This article explores Bhupi Sherchan’s overall viewpoint on the formation of a nation and the notion of a country. It will analyze the manner in which Bhupi Sherchan’s poetry influences the nation. It examines his efforts in nation-building through the theoretical lenses of nationalistic philosophers in Nepal, as well as the viewpoints of Renan, Gellner, and Anderson. The topic of country is extensively debated, and the researcher is enthusiastic about conducting research on this subject within the framework of Nepali literature. The researcher’s covering area includes the definition of the nation and the author’s use of it in their writing. The primary objective of my inquiry is to ascertain the correlation between literature and poets, specifically in connection to their perception of nationhood.